Release Kinetic Study of Matrix Type Transdermal Patch Using an Analgesic Drug - Mohit Saini; Sneha Singh; Amit Kumar; Lalit Parihar; Mukesh Kumar (IAR Journal of Medicine and Surgery Research, 2020)
Transdermal therapeutic systems are defined as a self-contained, distinct dosage forms which, when applied to the intact skin, deliver the drug, through the skin at control rate to the systemic circulation. TDDS characterizes one of the most quickly advancing areas of novel drug delivery. TDDS are designed for controlled liberate of drug through the skin into systemic circulation maintaining consistent efficacy and reducing dose of the drug and its related side effects. Present study was conducted to prepare transdermal patch of Tramadol HCL with permeation enhancer to diminish extra side effects and to provide sustain drug delivery. Various kinetics models were examined for optimized formulation. The drug release data of all the formulation were fitted to different kinetic models to find out the kinetics of drug release from transdermal patch. The drug release data was also fitted to zero order (cumulative amount of drug release vs. time) power equation to find out the drug release mechanism.